The Correlation between Plasma IL-17 Levels, Lymphocyte Counts, and Neutrophil Counts with the Colonisation of Candida sp. in Tuberculosis Patients with a Treatment History - Vycke Yunivita; Mutiara Anastasia; Intan Mauli Warma Dewi; Chrysanti Murad (Nusantara Medical Science Journal, 2025)
Introduction:  Tuberculosis (TB) patients with a history of ATT therapy are associated with changes in IL-17 levels, lymphocyte counts, and neutrophil counts. Increased IL-17 levels, lymphocyte counts and neutrophil counts indicate colonisation of Candida sp. fungus. Changes in the immune response in TB patients with Candida sp. colonisation may cause complications of TB that affect the treatment success rate. Methods:  This research was designed for observational analytical study with a cross-sectional design. 59 subjects are divided into 3 groups, consisting of 21 TB-positive people with Candida sp. colonisation, 21 TB-positive people without Candida sp. colonisation, and 17 TB-negative people with Candida sp. colonisation. Plasma IL-17 levels are examined using the ELISA test, while the lymphocyte and neutrophil counts are seen from previous study examinations (AFFECT). Results:   The plasma IL-17 levels in the TB-positive group with Candida sp. colonisation were 24.05 pg/ml (IQR 21.77-30.50). The plasma IL-17 levels in the TB-positive group without Candida sp colonisation were 23.08 pg/ml (IQR 19.11-32.46). The plasma IL-17 levels in the TB-negative group with Candida sp. colonisation is 20.72 pg/ml (IQR 18.51-22.84) pg/ml, (p=0.046). However, there are no statistically significant difference was observed in lymphocyte and neutrophil counts (p=0.078). Conclusions:  The differences in IL-17 levels that occur in the TB group with Candida sp colonisation may serve as an immunological signal suggesting the need for fungal assessment if the TB patients do not improve their treatment outcome after undergoing ATT for over 6 months.